Ricordi. Nuova edizione e introduzione storica - di Pagolo Morelli, Giovanni (Biblioteca di storia, 2019)
Giovanni di Pagolo Morelli's Ricordi, long known to historians, are published here for the first time in an integral version which is also linguistically faithful to the original manuscript. This new critical edition is accompanied by a long introductory essay on the author, the intentions of his work and the results it had by the heirs to whom it was addressed. The 74 years of Giovanni Morelli's life, from the 1370s to the mid 1440s, are placed in a decisive time span for the history of Florence, and they are marked by a strong social mobility of which the Morellis, a family with humble origins, were the protagonists. Reading the Ricordi, and combining them with the analysis of the substantial remaining documentation borne by the author and his family, help understand the strong push to social rise which animated Morelli, and the reasons for his descendants' position among Florence's prominent family scene of the late 15th century.